An Analysis of The Effect of Online Banking on Bank Performance in Indonesia - Swesti Mahardini; Santi Kurnia; Yusuf Maura; Pandu Haryanto; Yohn Piter Barus (Journal of Governance Risk Management Compliance and Sustainability, 2022)
Technology has become a necessity, including in financial institutions which are the backbone of economy, it can help to improve service delivery, simplify investigations, improve banking performance, and save transaction time.  It is expected that the bank can expand its services not only limited to receiving and sending cash. As a result, it is very important to assess the performance of banks as they are in a critical position of the globalization period. The study aims to analyze the effects of internet banking, mobile banking, and automated teller machines on bank performance as measured by asset returns, from commercially listed banks in Indonesia. The study uses quantitative methods and panel data analysis. The study used secondary data in the form of company annual reports. The samples used purposive sampling methods from the banking industry that met the criteria and were listed on the Indonesia Stock Exchange. Data analysis uses multiple regression methods. The tool used is Eviews 10 statistics program. The results showed internet banking had a significant negative effect, mobile banking and ATM have a significant positive effect on bank performance. Overall internet banking, mobile banking, and ATM simultaneously have a significant effect on banking performance. The study limits 36 samples of commercial banks registered in 2016-2020 and there are 3 independent variables and 1 dependent variable in analyzing bank performance. The study explains that not all banks implement a comprehensive internet banking in alternate of mobile banking.